THE IMPLEMENTATION OF GOOD ENVIRONMENTAL GOVERNANCE IN WASTE MANAGEMENT - Mustiqowati Ummul Fithriyyah; triyani ramadhiyanti; Tri Yuniningsih; Sunee Hongwiset (JURNAL ILMU SOSIAL, 2024)
Waste is a national problem in Indonesia that has not found an optimal solution and tends to get worse. Effective waste management for environmental preservation and extinction is one of the principles of good environmental governance. An important part of good governance is collaboration between the private sector and the community to achieve effective, efficient, and appropriate waste management. This study aims to assess the implementation of waste management in Tuah Karya Village. This study uses a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The results of the study show the implementation of Good Environmental Governance in waste management in Pekanbaru, with a focus on the steps that have been taken by local governments to build effective waste management in their respective regions. Several areas in Pekanbaru have implemented good waste management practices, such as building waste banks, recycling waste into new products, and promoting waste reuse. This study examines the forms of implementation of Good Environmental Governance in waste management in Pekanbaru. In the case of Waste Bank management in Tuah Karya, based on the principles of good environmental governance, it turns out that one of the seven principles, namely access to information, has not been able to achieve the goal of realizing a Smart City in Pekanbaru. This is because many residents are still unaware of the existence of the Waste Bank, and many are reluctant to participate. These challenges make it difficult for the Waste Bank to contribute to the ideals of Smart City in Pekanbaru.